Results of LIA-10M accelerator investigations - Gordeev, V.S.; Myskov, G.A.; Filippov, V.O.; Viktorov, I.V. (Вопросы атомной науки и техники, 2001)
There are presented basic results of experiments on the LIA-10M accelerator since its putting into operation (1994) till today. There were investigated various modes of accelerator operation and its output characteristics depending on the parameters of injected electron beam, number of connected accelerator modules, time program of inductors switch-in etc. There was obtained a large scope of experimental data that are of interest for LIA-10M accelerator practical use and for the development of new facilities of this type. The investigations that have been performed recently make it possible to considerably (half as much again) increase the output dose parameters of the accelerator as compared to the level achieved before: maximal dose (Si) and dose rate on the output flange constitute 400 Gy and 2.5.1010 Gy/s, while at a 1 meter distance from the target they are equal to 7.5 Gy and 5.108 Gy/s, respectively.